GROWTH HORMONE AND INSULIN-LIKE GROWTH FACTOR IN ADULTS WITH ARTERIAL HYPERTENSION - T. A. Mangileva (Российский кардиологический журнал, 2015)
Aim. To compare the concentration of growth hormone, insulin-like growth factor and the specifics of carbohydrate and lipid metabolism in AH patients of the 1st grade and the persons without elevated BP, to reveal a relation of these values with obesity rate and with the gender.Material and methods. Morning fasting blood was used for growth hormone, insulin-like growth factor, insulin, glucose, total cholesterol, high and low density lipoproteid cholesterol, triglycerides and C-reactive protein measurement in 43 patients with arterial hypertension of the 1st grade with overweight (18 persons) or obesity (25 persons), and in 31 participant with optimal and normal blood pressure with overweight (15 persons) or normal body mass.Results. The level of growth factor and its effector — insulin-like growth factor was lower (p<0,05) and body mass index was higher (p<0,001) in patients with increased blood pressure than in controls. In the main group also there was higher insulin concentration, higher total cholesterol, triglycerides and C-reactive protein. In comparison of two parameters only for the participants with excess body mass and high or normal blood pressure (excluding growth hormone concentration) all differences disappeared. Comparison of the two parameters mentioned in patients with arterial hypertension with and without obesity also did not reveal intergroup differences.We did not find gender dimorphism influence on the growth hormone and insulin-like growth factor secretion as well, as on the changes of lipid and carbohydrate metabolism. For the participants from the upper tercile by the level of insulin-like growth factor it was more common to have higher diastolic pressure than in lower tercile.Conclusion. The decrease of growth hormone concentration and insulin-like growth factor, as the changes in lipid and carbohydrates metabolism are common for the combination of 1 st grade arterial hypertension and obesity, although isolated blood pressure increase or the development of obesity does not influence these parameters significantly.